2011
DOI: 10.1093/rheumatology/ker134
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation end products cause collagen II reduction by activating Janus kinase/signal transducer and activator of transcription 3 pathway in porcine chondrocytes

Abstract: Blocking JAK/STAT3 signalling pathway inhibited AGE-induced activation of MMP-13 and ADAMTS and prevented AGE-mediated decrease of collagen II and proteoglycan (aggrecan). The results indicated that JAK/STAT3 pathway may be a potential target for designing disease-modifying drugs for the treatment of OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 33 publications
0
48
0
Order By: Relevance
“…The AGEs that accumulate in chondrocytes from older individuals appear to activate janus kinase 2 and 3 signal transducer and STAT 3 phosphorylation, and lead to increased MMP13 and ADAMTS-4 and -5 expression and activity (Huang et al. 2011). …”
Section: Articular Cartilagementioning
confidence: 99%
“…The AGEs that accumulate in chondrocytes from older individuals appear to activate janus kinase 2 and 3 signal transducer and STAT 3 phosphorylation, and lead to increased MMP13 and ADAMTS-4 and -5 expression and activity (Huang et al. 2011). …”
Section: Articular Cartilagementioning
confidence: 99%
“…Reports showed that disarrangement of F-actin cytoskeleton induced by activation of RhoA/ROCK signaling is the main mechanism in AGEs-RAGE injured endothelial cell hyperpermeability [8]. Moreover, AGE-RAGE initiates the cascades of signaling transduction such as AGE-RAGE-NADPH oxidase (Nox) to aggravate oxidative stress [9], or AGE-RAGE-Jak/Stat to interfere the biosynthesis of collagen in kidney fibroblast [10]. These downstream pathways are involved widely in inflammation, autophagy, and apoptosis exerting an extend influence on cellular metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to affecting the mechanical properties of tissue, AGEs also affect cell function via the engagement of receptor for AGEs (RAGE), which is the best characterized AGE receptor. AGEs/RAGE stimulate the activation of nuclear factor-κB (NF-κB)-dependent pathways and increase oxidative stress, subsequently inducing production of proinflammatory mediators including tumor necrosis factor-α (TNF-α) and matrix metalloproteinases (MMPs) [8,9]. However, it is recognized that current treatments to interrupt AGE-related signal pathways are inefficient, which limits the efficient treatment for OA.…”
Section: Introductionmentioning
confidence: 99%